A DISCOURSE ANALYSIS OF POEMS ENTITLED “THE NEGRO SPEAKS OF THE RIVER” BY LANGSTON HUGHES SURAKARTA IN 2021/2022 ACADEMIC YEAR - Ricky Aziz Mahendra; Ch. Evy Tri Widyahening (English Research Journal : Journal of Education, Language, Literature, Arts and Culture, 2023)
The objectives of this research were: 1) To find out the analysis context namely Cultural, Social context and Inferential in these poems written by Langston Hughes entitled The Negro Speak Of The River ; 2) To find out the grammatical aspect in Langston Hughes’s poems entitled Negro speaks of the river ; 3) To find out the lexical aspect in Langston Hughes’s poems entitled Negro speaks of the river   The researcher used qualitative research as research method with the type of library research. This research used primary and secondary data as the sources .The techniques of data collection were retrieving the poem of Langston Hughes The Negro Speaks of The River , reading the poem several time, focusing on the sentences of the poems namely the diction, and the figurative word, selecting data, classifying the data, displaying the data, analysing data, interpreting the data, and making the conclusion. In technique of analyzing data, the researcher used interactive data analysis by Miles and Huberman, such as data collecting, data reduction, data displaying, conclusion and verification. To find the validity of the research, was used by triangulation data.   The results of the researcher show that: 1) The Cultural Context, Social Context, and Inferential of poems entitled The Negro Speaks of The Rivers were about the influence of blacks history as a slaves and about the inequity for Blacks. The Social Context were about, racialism and discrimination and about struggling. The Inferential were about refering a longest river as a history of Black people, and giving advice about life condition and also about struggle. 2) The Grammatical aspect in poems The Negro Speaks of The Rivers, were: Reference includes “I”, “Me”, “My”, “It”, “He”, “you”, “rivers”, “vein”, pyramid”, “Ancient dusky”, “the Euphrates”, “the Congo”, and “the Mississippi”. The Conjunction in these poems were “as”, “and”, and “when”. 3) Lexical Aspect in poems The Negro Speaks of The Rivers were: Repetition in these poems were Assonance use vowel /o/ sound, and Consonant Repetition. Synonym in these poems were “ancient…and older”. Collocation in these poems were “I’ve” “I’ll”, “ain’t”, “don’t”, “it’s”, and “I’se”. This research result showed the Cultural Context, Social Context, and Inferential of these poems was refers to the history of Black People in America as a slaves. The Grammatical and Lexical Aspects also presented in these poems. The research result can be useful for teaching material especially in grammatical and lexical.   Keywords: Langston Hughes, Poems, A Descriptive Qualitative, Discourse Analysis